Ketoacidosis and otitis media as a potencial cause of cerebral venous thrombosis in a 7-year-old boy - Lipińska, Justyna; Lipiński, Łukasz; Kowalczuk, Maria; Kopeć, Izabela; Mitek-Palusińska, Joanna; Woźniak, Magdalena (Journal of Education, Health and Sport, 2022)
Cerebral venous sinus thrombosis (CVST) in childhood is a rare disorder, occurring most often in the neonatal period, with mortality approaching 10%. This condition has multifactorial etiology including common childhood illnesses such as fever, infection, dehydration, and anemia, as well as acute and chronic medical conditions such as congenital heart disease, nephrotic syndrome, and malignancy. Thrombosis can also develop and propagate in response to local venous stasis. A large number of children have coincident local head or neck pathology, including head trauma, brain tumors, or recent intracranial surgery. Clinical symptoms are frequently nonspecific and include seizures, depressed level of consciousness, coma, lethargy, nausea, vomiting, headache, visual impairment, papilledema, and hemiparesis, which may often obscure the diagnosis and delay treatment. In the case of patients with neurological symptoms, imaging studies such as computed tomography (CT) and magnetic resonance imaging (MRI) are invaluable in diagnostics of various pathologies of the nervous system, because of their non-invasiveness, high sensitivity, and specificity. Early diagnosis with management along with a plan for secondary prevention can save from catastrophic consequences.